Issues of organization of stable passage of transit freight trains on the railway lines in accordance with technical and technological features of operation of technical stations and running sections - L. A. Muginshtein; M. I. Mekhedov (Вестник Научно-исследовательского института железнодорожного транспорта)
Determination of the actual capacity of rail lines, taking into account technical and technological features of operation of technical stations and running sections is one of the most important systemic problems facing the industry. In order to solve the problem a dynamic mathematical model was developed where the number of receiving-departure tracks in technical station yards, time for holding tracks for handling transit cargo trains, intervals of following trains passing in train flows in up-and-down directions connected by the system of interdependencies. The model allows to reduce train-hours and to increase local speed at the passage of train flows due to optimization of ratios of holding time of receiving-departure tracks, number of such tracks and values of intertrain intervals. By means of dynamic model the reasons of increase in holding time of tracks in up-train yards of the st. Karymskaya at increase in number of receiving-departure tracks are explained. Direction of increasing capacity of up-train yards at st. Karymskaya is the consistent implementation of measures to ensure daily provision of locomotives, serving the Eastern operation area, at the st. Karymskaya in rate of 5 - 10 locomotives and relevant receive of up-train flows from the next road in the amounts determined by real available capacity at the st. Karymskaya, changed after creating a locomotive reserve.